Hydrothermal synthesis of ZnO nanorods - Tang, Jie. (2009)
Since the piezoelectric properties of zinc oxide (ZnO) were discovered in 1960, the investigations in applications of ZnO in electronics, optics and photonics have drawn large attention to the scientific as well as industrial fields. When it came to recent decades, nanotechnologies brought the research to a new era. Nanostructured materials offer not only better performance to electrical and optical devices but also a great convenience to life. This project aimed to synthesize ZnO nanorods with uniform size and relatively high aspect ratio via a simply hydrothermal method. Zn(NO3)2 and HMT were used as the precursors for synthesis of ZnO nanorods. Experimental conditions such as reactant concentrations, reaction time and temperature were varied in experiments to investigate their effects on the characteristics of the synthesized ZnO nanorods respectively. CTAB was used as a surfactant to incorporate in the synthesis of ZnO nanorods with varied synthesizing conditions. A discrepant observation on the effect of reactant concentration on the morphology and CTAB on the crystallinity of ZnO nanorods with reported work was obtained and will be discussed.